A Study on Problems of the Street Vendors in Lalbandi Municipality - Chaudhary, Birendra (Janajyoti Journal, 2024)
Due to their lack of education and skills, street vendors are among the most vulnerable and impoverished groups in the urban informal labor market and business sector. They are also unable to obtain permanent positions in the lucrative formal sector. They constantly attempt to use their limited financial means to address the issues affecting their way of life. They serve as the primary distribution routes for a wide range of goods used on a daily basis, including fruits, vegetables, shoes, ready-made clothes, toys, household appliances, stationery, newspapers, and periodicals. A serious dilemma would arise for small-scale businesses that cannot afford to retail their products through pricey formal sector distribution networks, as well as fruit and vegetable growers, if they were to be removed from urban markets. So is found in the case of street vendors of Lalbandi Municipality. Thus, main purpose of conducting this study is to find out the problems faced by street vendors in Lalbandi Municipality. For this, descriptive research design is adopted to explore street vendors’ problems. Out of two hundred seventy-three street vendors of Lalbandi Municipality, thirty street vendors are chosen randomly. The street vendors who sell fruits, vegetables, prepared foods, and household appliances via local vehicles and permanent shelter are the subjects of the current study. The study showed that there is a noteworthy correlation between the issues encountered by the street vendors. The respondents’ general opinion of street sellers and the issues they encountered do not significantly correlate. In nutshell, the street vendors of Lalbandi Municipality have been facing various sorts of problems such as lack of security, price fluctuation, lack of sufficient amount, bribes to the authorities etc. and for that a comprehensive strategy that includes social protection measures, infrastructure and service investments, policy reforms, and initiatives to organize and empower street vendors is needed. Furthermore, the present study is useful to the stakeholders, policy makers and to those who have just started up their small-scale businesses.